8 Great Ormond Street Hospital (GOSH) Summer School 2020: lessons on designing a digital conference. (30th November 2020) - Liu, Shuang; Smith, Jonathan; Tutt, Abbie; Poisson, Justin; Blackburn, Simon; Willock, Marissa; Poisson, Jeroen; Palmer, Nicola; Brown, Shereen; Wheeler, Olivia; Stow, Peter; McGonegal, Ellie; et al.
Abstract : Background: GOSH Summer School (GSS) is a conference for medical students and early career trainees. It has been run as a face-to-face event in the previous two years. COVID-19 outbreak challenged us to reformat the conference digitally. Methods: The GSS was run over four days, and the programme had main themes on each day: General Paediatric, Surgery and Innovation, Global health and COVID, and Paediatric Sub-specialties. The conference was hosted as webinar/Q&A sessions; questions were submitted via a digital platform with anonymous options. Participants were encouraged to interact via conference App. Results: 60% of the registrations were medical students from year 4 and 5. 630 different users logged in to the conference, with an average of 300 participants per session compared to 50–75, in the previous two years. According to the daily polls, GSS was the first virtual conference for 59% of the participants since the pandemic; 58% preferred to ask questions using an online written platform, 4% preferred to speak directly, and 38% chose both. About the most productive method to deliver education, 36% chose face-to-face sessions, 34% Webinars, and 22% felt these two methods were considered equal. 78% voted that our format of 30 minutes presentation with 15 minutes Q &A was 'about right.' 69% felt our current format of 4–5 hours per day of webinar time was considered the best option. About 227 participants joined the conference App. 346 participants completed the post-conference survey, and 100% voted to continue the online format for next year's conference. Discussion: The online GSS was as successful as the previous face-to-face events. We have learned that digital platforms can efficiently deliver high-quality education, promote interaction and engagement with the participants, and reach a larger number of students.